Tıbbi Perfüzyon Pompası Tasarımı - Yeter, İsmail (Fen Bilimleri Enstitüsü, 2014)
Yeter, İsmail. Minimal Noninvaziv Tıbbi Cihaz: Modüler Perfüzyon Pompası. Yüksek Lisans Tezi. İstanbul, 2014. Teknolojinin medikal alandaki yansımalarının, insan sağlığında yeri doldurulamaz bir halde olduğu aşikardır. Gelişen teknolojiyle birlikte otokontrollü sistemler; kesinlik, hassasiyet ve zaman gibi hayati önem taşıyan kriterlerde insana kıyasla daha fazla yer edinmişlerdir. İnsana bağlı faktörlerin kişiden kişiye, durumdan duruma değişiklik göstermesi sağlık sektöründe tahammül edilemeyecek hatalara yol açabilmektedir. Ayrıca ilacın doğru, kararlı ve tekrarlanabilir dozajlanması tedavi için olmazsa olmazlar arasındadır. Bu değerler dorultusunda içsel kontrolünü yaparak istenilen kararlılıkta ve tekrarlanabilir çıktılar verebilen sistemlerin gerekliliği günümüzde mecburi hale gelmiştir. Kontrollü ilaç salınımıda son zamanlarda önem kazanan, üzerine çalışmalar yapılan bir konudur. Perfüzyon ve infüzyon pompaları kontrollü ilaç salınımının temel öğelerindendir. Bu tip pompalar hastanelerin yoğun bakım ünitelerinde, servislerde, evde tedavide kullanılabilmekte hatta implant haline getirilebilmektedir. Kontrollü ilaç salınım pompalarının farklı tip ve özelliklerde birçok çeşidinin bulunmasıyla birlikte temel olarak bu pompalar medikal sıvının istenilen miktarda ve hızda hastaya aktarılması amacı ile kullanılmaktadır. Hedef; kullanımda olan kontorollü ilaç salınım cihazlarına alternatif oluşturarak tedavi süreçlerindeki eksikliğin giderilmesidir. Bu geliştirilen sistem ile sağlık personelinin yoğun stres altındaki çalışması hafifletilecek ve zaman tasarrufu sağlayacaktır. Bu tarz sistemlerin sağlık sektöründe kullanılması ile çalışma verimi arttırılmış olacaktır. Hastalar açısından bakıldığında ise maruz kalınan fiziki müdahalelerin azaltılması ile tedavi, idame ve toparlanma süreçlerinin hızlı ve etkili olması sağlanacaktır. Çalışmada; bağımsız çalışabilen ve merkezi sisteme veri aktarımı yapabilen bir mobil pompa sisteminin tasarımı ve prototipi gerçekleştirilmiştir. Sistem tek kontrol birimi ile farklı özelliklere sahip mekanik üniteleri kontrol edebilmektedir. Her bir modül kendi başına çalışabilmekte, dahili kontrol birimleri ile güvenli şartlar altında çalışmayı sürdürebilmektedir. Ayrıca, bu modüller yuvalarından kolayca ayrılabilmekte, seyahat durumunda bile çalışmasını idame ettirmektedir. Sistem tasarımında ARM tabanlı mikrodenetleyici, Grafik LCD ekran, step motor kontrol sistemi, dahili batarya, yatay mekanik aksam ve süreç izleme için sensörler-algılayıcılar kullanılmıştır. Yapılan bu çalışma ile hali hazırda kullanılan pompalara ek olarak otokontrol sistemi ile çalışma kalibrasyon testi yapılması sağlanmıştır. Bu sayede sağlık çalısanları ve hasta açısından güven duygusunu arttıracak, kullanımda kolaylık ve zaman tasarrufunu sağlayabilecek bir ürün ortaya konmuştur.

In the past, the treatment of illness has been accomplished by administering drugs to the human body via various dosage forms, like pill. These traditional products are still commonly seen today. To achieve and maintain the drug concentration in the body within the therapeutic range required for a medication, it is often necessary to take this type of drug delivery system several times a day. A number of advancements have been made recently in the development of new techniques for drug delivery. These techniques are capable of regulating the rate of drug delivery, sustaining the duration of therapeutic action, and/or targeting the delivery of drug to a specific tissue. Drug delivery refers to approaches, formulations, technologies, and systems for transporting a pharmaceutical compound in the body as needed to safely achieve its desired therapeutic effect. These controlled drug delivery systems that could provide the following benefits:  Controlled administration of a therapeutic dose at a desirable rate of delivery,  Maintenance of drug concentration within an optimal therapeutic range,  Maximization of efficacy-dose relationship,  Reduction of adverse side effects,  Minimization of the needs for frequent dose intake,  Enhancement of patient compliance. An external infusion pumps is a medical device used to deliver fluids into a patient’s body in a controlled mannes. There are many different types of infusion pumps, which are used for a variety of purposes and in a variety of environments. Infusion pumps may be capable of delivering fluids in large or small amounts, and may be used to deliver nutrients or medications – such as insulin or other hormones, antibiotics, chemotherapy drugs, and pain relievers. A number of commonly used infusion pumps are designed for specialized purposes. These include: Enteral pump - A pump used to deliver liquid nutrients and medications to a patient’s digestive tract. Patient-controlled analgesia (PCA) pump - A pump used to deliver pain medication, which is equipped with a feature that allows patients to self-administer a controlled amount of medication, as needed. Insulin pump - A pump typically used to deliver insulin to patients with diabetes. Insulin pumps are frequently used in the home. Infusion pumps may be powered electrically or mechanically. Different pumps operate in different ways. For example: In a syringe pump, fluid is held in the reservoir of a syringe, and a moveable piston controls fluid delivery. In an elastomeric pump, fluid is held in a stretchable balloon reservoir, and pressure from the elastic walls of the balloon drives fluid delivery. In a peristaltic pump, a set of rollers pinches down on a length of flexible tubing, pushing fluid forward. In a multi-channel pump, fluids can be delivered from multiple reservoirs at multiple rates. A smart pump is equipped with safety features, such as user-alerts that activate when there is a risk of an adverse drug interaction, or when the user sets the pump s parameters outside of specified safety limits. In this thesis, the scientific concepts and technical principles behind the development of this new generation of intraveneous perfusion pump systems are outlined and discussed. The electronic part of the system consists of two different boards. The first PCB board is the control board. Control board consists of microcontroller, ADC circuits, buzzer, LCD display etc. In this thesis, STM32F105VCT6 microcontroller is selected for synchronising, programing, step motor driving, system controlling, data transfering and ADC reading. Since there is only 256 Kbyte Flash memory, we can it repeatedly tested to minimize using extra Eprom memory. 240x64 pixel Graphic LCD display is used to give information about infusion process. The second PCB is the power board. This board is designed to convert 220VAC to +12V, +5V and 3.3V DC. Converting process be done two types voltage regulator IC s. These voltage regulator IC s are smps circuit, 7805 and AMS1117-3.3 IC’s. +12V DC voltage is produced by SMPS type regulator. Also the board consist of a step motor driver IC (ULN2064B) and battery charger IC (MCP73844). In this project, a unipolar stepper is used. The software of the system is developed on Mikroelektronika MicroC for ARM IDE. The designs of the electronic circuits are designed on ALTIUM software (V. 10.391), and test of circuits are performed on Proteus ISIS software (V. 7.7). As a result In this study, intensive care units of hospitals in terms of health care workers and provide a great convenience and time savings as well as intervention in patients exposed to serve less of a physical product have been revealed.
Medical Perfusion Pump
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: perfüzyon pompası; şırınga pompası; infüzyon pompaları; intravenöz girişim; perfüzör; perfusion pump; syringe pump; infusion pump; intravenous treatment